Expression of Semaphorins, Neuropilins, VEGF, and Tenascins in Rat and Human Primary Sensory Neurons after a Dorsal Root Injury - Lindholm, Tomas; Risling, Mårten; Carlstedt, Thomas; Hammarberg, Henrik; Wallquist, Wilhelm; Cullheim, Staffan; Sköld, Mattias K. (Frontiers in Neurology, 2017)
Dorsal root injury is a situation not expected to be followed by a strong regenerative growth, or growth of the injured axon into the central nervous system of the spinal cord, if the central axon of the dorsal root is injured but of strong regeneration if subjected to injury to the peripherally projecting axons. The clinical consequence of axonal injury does lead to loss of sensation and may also lead neuropathic pain. In this study we have used in situ hybridization to examine the distribution of mRNAs for the neural guidance molecules semaphorin 3A (SEMA3A), semaphorin 3F(SEMA3F) and semaphorin 4F(SEMA4F), their receptors neuropilin 1 (NP1) and neuropilin 2 (NP2) but also for the neuropilin ligand vascular endothelial growth factor (VEGF) and Tenascin J1, an extracellular matrix molecule involved in axonal guidance, in rat dorsal root ganglia (DRG) after a unilateral dorsal rhizotomy (DRT) or sciatic nerve transection (SNT). The studied survival times were 1-365 days. The different forms of mRNA´s were unevenly distributed between the different size classes of sensory nerve cells. The results show that mRNA for SEMA3A was diminished after trauma to the sensory nerve-roots in rats. The SEMA3A receptor NP1, and SEMA3F receptor NP2, was significantly up regulated in the DRG neurons after DRT and SNT. SEMA4F was up regulated after a SNT. The expression of mRNA for VEGF in DRG neurons after DRT showed a significant up regulation that was high even a year after the injuries. These data suggest a role for the semaphorins, neuropilins, VEGF and J1 in the reactions after dorsal root lesions.